Customer Relationship Management Menggunakan Metode Prototyping Untuk Produk Pembiayaan BPRS Al-Salam - Siti Anisah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
BPRS Al Salam is a Sharia Micro Finance Institution (LKMS) that already has many customers, especially in financing products. However, in the manual funding application, the customer must come to BPRS Al Salaam, this is very troublesome for customers who want to apply for financing. Financing type marketing media still uses brochures, there is no easily accessible media to find out information on customer financing data such as financing status, payment maturity from financing transactions and the absence of a special forum for communication between BPRS and customers. To improve service to customers of BPRS is the application of the concept of customer relationship management (CRM). The purpose of this study is to design a CRM for financing products in order to improve service to customers. The system development method uses the Prototyping method. Tools in designing systems using UML include usecase diagrams, narrative usecase, activity diagrams, sequence diagrams, and class diagrams. Whereas system programming uses PHP and MySQL database, system testing with user acceptance test (UAT) methods. The results of this study resulted in a CRMS (customer relationship management system) developed with the Kalakota and Robinson approach that would produce a system that was in accordance with the needs of the organization and concluded that 80% of users agreed that the BPRS interface and application features were made in accordance with desires.